2020
DOI: 10.1085/jgp.201812297
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ion selectivity in ASIC1a- and ASIC2a-containing acid-sensing ion channels

Abstract: Trimeric acid-sensing ion channels (ASICs) contribute to neuronal signaling by converting extracellular acidification into excitatory sodium currents. Previous work with homomeric ASIC1a implicates conserved leucine (L7′) and consecutive glycine-alanine-serine (GAS belt) residues near the middle, and conserved negatively charged (E18′) residues at the bottom of the pore in ion permeation and/or selectivity. However, a conserved mechanism of ion selectivity throughout the ASIC family has not been established. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 49 publications
6
22
0
Order By: Relevance
“…Interestingly, unlike pentameric ligand gated ion channels whose open state pore tends to collapse in molecular dynamics simulations (Damgen & Biggin, 2020), the open state of cASIC1 is reasonably stable, allowing more detailed examination of ion selectivity (Lynagh et al . 2017, 2020). However, these studies were not aimed at addressing how protonation drives transitions between functional states.…”
Section: The Basics Of Asicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, unlike pentameric ligand gated ion channels whose open state pore tends to collapse in molecular dynamics simulations (Damgen & Biggin, 2020), the open state of cASIC1 is reasonably stable, allowing more detailed examination of ion selectivity (Lynagh et al . 2017, 2020). However, these studies were not aimed at addressing how protonation drives transitions between functional states.…”
Section: The Basics Of Asicsmentioning
confidence: 99%
“…Indeed, past molecular dynamics work has explored interactions with psalmotoxin (Pietra, 2009), investigated a predicted calcium site at the extracellular mouth of the pore for ASIC3 (Zuo et al 2018), as well as studied the stability of a conserved salt bridge (Yang et al 2012) and the effects of mutations on dynamics (Roy et al 2013). Interestingly, unlike pentameric ligand gated ion channels whose open state pore tends to collapse in molecular dynamics simulations (Damgen & Biggin, 2020), the open state of cASIC1 is reasonably stable, allowing more detailed examination of ion selectivity (Lynagh et al 2017(Lynagh et al , 2020. However, these studies were not aimed at addressing how protonation drives transitions between functional states.…”
Section: Protonating Asics In Computational Simulationsmentioning
confidence: 99%
“…Furthermore, both approaches rely on ribosomal tolerance, which means certain backbone or side chain types cannot be incorporated (see section on Semi-synthetic approaches below). Lastly, and depending on the sequence context, incorporation efficiency can be highly variable, unwanted re-initiation from non-canonical start codons can occur or introduced stop codons can be read through, resulting in non-specific incorporation of (endogenous) amino acids at the site of interest (Kalstrup & Blunck, 2015;Lynagh et al 2018Lynagh et al , 2020Poulsen et al 2019;Khoo et al 2020). The latter issues are particularly problematic in the most N-and C-terminal parts of proteins.…”
Section: Nonsense Suppression With Orthogonal Trnas In Xenopus Laevismentioning
confidence: 99%
“…Lastly, and depending on the sequence context, incorporation efficiency can be highly variable, unwanted re‐initiation from non‐canonical start codons can occur or introduced stop codons can be read through, resulting in non‐specific incorporation of (endogenous) amino acids at the site of interest (Kalstrup & Blunck, 2015; Lynagh et al . 2018, 2020; Poulsen et al . 2019; Khoo et al .…”
Section: Genetic Modification Of Proteinsmentioning
confidence: 99%
“…Previous work indeed suggests that the selectivity filter of ENaCs is formed by the S of the G/SXS motif [19] and most ASIC structures available to date display a marked constriction at the level of this highly conserved M2 sequence feature [21, 22]. However, we have recently shown that the ASIC GAS sequence is unlikely to make major contribution to ion selectivity in ASIC1a and 2a, while acidic side chains in the lower M2 appear to be more important [17, 23]. Additionally, the latest ASIC structures show that the lower pore is lined by a reentrant loop formed by side chains from the N-terminus [22], and this pre-M1 region has previously been implicated in ion selectivity in ASICs [24, 25] and ENaCs [26, 27].…”
Section: Introductionmentioning
confidence: 99%